(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In order for the nanomaterials to be utilized, it is vital to be able to control the structural properties of the Mn-Zn-ferrites nanoparticles (NPs) by sol-gel and Mn-Zn-ferrites /TiO2 nanocomposite (NC) generated by sol – gel method at 650, 750, and 850 oC. An examination into the possibility of producing the Mn-Zn-ferrites by sol-gel and Mn-Znferrites /TiO2 (NC) as prospective structure-tunable nanomaterials is described in this report. X-ray diffraction (XRD), field emission-scanning electron microscopy (FE-SEM), and Fourier-transform infrared (FTIR) spectroscopy were used to characterize the structural properties of the Mn-Zn-ferrites by sol-gel and Mn-Zn-ferrites /TiO2 (NC). They were 27 to 30 nm in size with a cubic structure, while the Mn-Zn-ferrites /TiO2 (NC) were 10 to 30 nm in size with a cubic structure. FE-SEM images showed the synthesized the Mn-Zn-ferrites and the Mn-Zn-ferrites /TiO2 (NC) had a nanoparticlelike structure with a particle size of 27.77, to 72.04 nm. The strong FT-IR absorption peaks at 500 and 600 cm-1 represented an Fe-O, Mn-O, and Zn-O vibration band and 1667 cm-1 represented an TiO2 for the Mn-Zn-ferrites and the Mn-Zn-ferrites /TiO2 (NC), respectively.